2012
DOI: 10.2147/ijn.s33612
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotube interaction with extracellular matrix proteins producing scaffolds for tissue engineering

Abstract: Abstract:In recent years, significant progress has been made in organ transplantation, surgical reconstruction, and the use of artificial prostheses to treat the loss or failure of an organ or bone tissue. In recent years, considerable attention has been given to carbon nanotubes and collagen composite materials and their applications in the field of tissue engineering due to their minimal foreign-body reactions, an intrinsic antibacterial nature, biocompatibility, biodegradability, and the ability to be molde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 169 publications
(195 reference statements)
1
15
0
Order By: Relevance
“…We intended to modify our DBPECM in its native hydrated form using HTE approach suitable for TEHV and optimized a protocol that resulted in hydrophilic Bio-Hybrid scaffold with a contact angle similar to that of BP (Table 1). A previous study demonstrated that HTE using ECM gel resulted in increased mechanical strength but compromised the 3D structure that favours cellular adhesion, retains hydrophilicity and helps in cellular differentiation [25,34]. Our protocol also retained the native 3D structure of BP for development of an improved scaffold for valve fabrication without processing and compromising the tensile strength (Table 1).…”
Section: Discussionmentioning
confidence: 80%
“…We intended to modify our DBPECM in its native hydrated form using HTE approach suitable for TEHV and optimized a protocol that resulted in hydrophilic Bio-Hybrid scaffold with a contact angle similar to that of BP (Table 1). A previous study demonstrated that HTE using ECM gel resulted in increased mechanical strength but compromised the 3D structure that favours cellular adhesion, retains hydrophilicity and helps in cellular differentiation [25,34]. Our protocol also retained the native 3D structure of BP for development of an improved scaffold for valve fabrication without processing and compromising the tensile strength (Table 1).…”
Section: Discussionmentioning
confidence: 80%
“…These results coupled with the ability to fine tune surface roughness of 3D carbon nanotube scaffolds by using nanotubes of varying diameters suggest that 3D all-carbon scaffolds may be exploited to control/govern cell fate purely based on nanotopographic cues. In addition, nanostructured scaffolds offer several advantages over conventional polymeric scaffolds such as (1) a single cell can contact millions of nanofibers (for example MWCNTs and SWCNTs), thereby resulting in the effective transmission of subtle topographic cues from the underlying scaffold substrate to the cell and (2) nanotopography and surface roughness of MWCNT and SWCNT scaffolds may result in a better host-implant integration reducing the risk of failure of biomedical implants [65]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition to mineral nanoparticles, collagen matrices have been doped with carbon [194], silver [195] and gold [196] nanoparticles. Carbon nanotubes are of particular interest because they are on the same size scale as collagen fibrils, with diameters on the order of nanometers and lengths on the order of microns.…”
Section: 0 - Modifying the Properties Of Collagen Biomaterialsmentioning
confidence: 99%